Investigating Attributes of Oil Source Rocks by Combining Geochemical Approaches and Basin Modelling (Central Gulf of Suez, Egypt) - Moataz Barakat; Mohamed Reda; Dimitra E. Gamvroula; Robert Ondrak; Dimitrios E. Alexakis (Resources, 2025)
The present study focused on the Upper Cretaceous to Middle Miocene sequence in the Central Gulf of Suez, Egypt. The Upper Cretaceous to Middle Miocene sequence in the October field is thick and deeply buried, consisting mainly of brown limestone, chalk limestone, and reefal limestone intercalated with clastic shale. This study integrated various datasets, including total organic carbon (TOC), Rock-Eval pyrolysis, visual kerogen examination, vitrinite reflectance (%Ro), and bottom-hole temperature measurements. The main objective of this study is to delineate the source rock characteristics of these strata regarding organic richness, thermal maturity, kerogen type, timing of hydrocarbon transformation and generation. The Upper Cretaceous Brown Limestone Formation is represented by 135 samples from four wells and is considered to be a fair to excellent source rock, primarily containing type I and II kerogen. It is immature to early mature, generating oil with a low to intermediate level of hydrocarbon conversion. The Eocene Thebes Formation is represented by 105 samples from six wells and is considered to be a good to fair oil source rock with some potential for gas, primarily containing type II and II/III kerogen. Most samples are immature with a low level of hydrocarbon conversion while few are mature having an intermediate degree of hydrocarbon conversion. The Middle Miocene Lower Rudeis Formation is represented by 8 samples from two wells and considered to be a fair but immature source rock, primarily containing type III kerogen with a low level of conversion representing a potential source for gas. The Middle Miocene Belayim Formation is represented by 29 samples from three wells and is considered to be a poor to good source rock, primarily containing kerogen type II and III. Most samples are immature with a low level of hydrocarbon conversion while few are mature having an intermediate degree of hydrocarbon conversion. 1D basin model A-5 well shows that the Upper Cretaceous Brown Limestone source rock entered the early oil window at 39 Ma, progressed to the main oil window by 13 Ma, and remains in this stage today. The Eocene Thebes source rock began generating hydrocarbons at 21.3 Ma, advanced to the main oil window at 11 Ma, and has been in the late oil window since 1.6 Ma. The Middle Miocene Lower Rudeis source rock entered the early oil window at 12.6 Ma, transitioned to the main oil window at 5.7 Ma, where it remains active. In contrast, the Middle Miocene Belayim source rock has not yet reached the early oil window and remains immature, with values ranging from 0.00 to 0.55 % Ro. The transformation ratio plot shows that the Brown Limestone Formation began transforming into the Upper Cretaceous (73 Ma), reaching 29.84% by the Miocene (14.3 Ma). The Thebes Formation initiated transformation in the Late Eocene (52.3 Ma) and reached 6.42% by 16.4 Ma. The Lower Rudeis Formation began in the Middle Miocene (18.7 Ma), reaching 3.59% by 9.2 Ma. The Belayim Formation started its transformation at 11.2 Ma, reaching 0.63% by 6.8 Ma.